WRITING NARRATIVE TEXTS BASED ON MIND MAPPING IN PRIMARY SCHOOLS - Fransiska Jaiman Madu; Mariana Jediut (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
The ability to write texts for primary school students is low. Writing with good structure and coherence, and using the correct rules of the Indonesian language, seems difficult. This study aims to describe the text-writing skills of primary school students and the challenges they face. This research uses a mixed-methods approach with a sequential explanatory design. In practice, this mixed-methods approach combines qualitative and quantitative methods. Furthermore, this study uses student-composed texts as its data source. Fifteen grade IV students from SDI Cuncalawir provided the data. Data were collected through a text-writing test using concept maps. The value given is guided by indicators of text writing based on concept maps. The quantitative assessment guidelines for the text in question consist of the following: conformity of content with the concept map (score 20), writing structure (score 20), completeness of ideas (score 20), cohesion/coherence between paragraphs (score 20), and creativity in developing ideas (score 20). The assessment was based on a rubric. The results show that using concept maps helped the students with their writing. This is evident in the scores obtained by students in the 'Excellent' category. It is therefore suggested that teachers continue to use concept maps by setting students further challenges, such as enriching the content of concept maps with explanations.